If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 = 26x + -34 Reorder the terms: 18 = -34 + 26x Solving 18 = -34 + 26x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-26x' to each side of the equation. 18 + -26x = -34 + 26x + -26x Combine like terms: 26x + -26x = 0 18 + -26x = -34 + 0 18 + -26x = -34 Add '-18' to each side of the equation. 18 + -18 + -26x = -34 + -18 Combine like terms: 18 + -18 = 0 0 + -26x = -34 + -18 -26x = -34 + -18 Combine like terms: -34 + -18 = -52 -26x = -52 Divide each side by '-26'. x = 2 Simplifying x = 2
| 82+(-20)= | | 8x+13y=2700 | | 4x^2+9-45=0 | | ysinx-xy^2=c | | ysenx-xy^2=c | | x^2-8x+16=-27 | | -41+(-25)= | | (x^(3/8))(x^(-7/10)) | | -3(x+2)-42=5-38 | | -41+(-15)= | | 12x+15=9(x+8) | | (3x+1)(x+2)=0 | | cosx=-0.72 | | y+(-22)=-46 | | (-7x+1)(10x+9)= | | (3m+1)(mx+2)=0 | | 15+y=13 | | 191=23x-85 | | -9-6=10x+9-9x | | -9-6=10x+9-9 | | -7(x+2)-13=14+8 | | 12x-51=6 | | 8(y+3)=24 | | 85-23+x=191 | | 5x^2+11y^2+16xy-36=0 | | 8x=-1701 | | -(4x-11)+4(3x+4)= | | -4-8=2 | | -31-4x=5-(1+5x) | | -0.5(-4x+3)-2=1+2x | | 3(-4)-(-13)= | | f(-8)=2x^2+4x+4 |